The Effect of Financial Socialization and Financial Literacy on Financial Satisfaction at PT Pegadaian With Financial Risk Attitude as a Mediating Variable - Ulwiyah, Arini; Raprayoga, Rusdi; Indriyano, Eka (Jurnal Pendidikan Ekonomi, 2026)
The increase in investment in Indonesia reflects a growing trend, driven by the modernization of digital platforms that make it easier for the public to access various investment instruments. This is also evident in the services offered by PT Pegadaian, which continues to innovate through digital platforms, such as apps and online services. This increase in investment activity indirectly boosts consumer satisfaction among the Indonesian public, including the consumer-oriented segment. However, it also contributes to individuals lacking clear long-term financial goals. Consequently, this leads to a decline in quality of life and psychological well-being. This study aims to analyze the influence of financial socialization and financial literacy on financial satisfaction, with financial risk attitude serving as a mediating variable among PT Pegadaian’s customers.This study employed a quantitative approach involving the distribution of a survey questionnaire to 150 respondents. The data analysis technique used was Partial Least Squares (PLS). The results indicate that financial socialization and financial literacy have a significant effect on financial satisfaction and financial risk attitude. Furthermore, financial risk attitude has a significant effect on financial satisfaction and mediates the relationship between financial socialization and financial literacy on financial satisfaction.